Immunonutrition Support for Patients Undergoing Surgery for Gastrointestinal Malignancy. Issue 29 (July 2015) - Song, Guo-Min; Tian, Xu; Zhang, Lei; Ou, Yang-Xiang; Yi, Li-Juan; Shuai, Ting; Zhou, Jian-Guo; Zeng, Zi; Yang, Hong-Ling; Pamela, von Reisswitz.
<x xml:space="preserve">Abstract</x> Abstract Enteral immunonutrition (EIN) has been established to be as a significantly important modality to prevent the postoperative infectious and noninfectious complications, enhance the immunity of host, and eventually improve the prognosis of gastrointestinal (GI) cancer patients undergoing surgery. However, different support routes, which are the optimum option, remain unclear. To evaluate the effects of different EIN support regimes for patients who underwent selective surgery for resectable GI malignancy, a Bayesian network meta-analysis (NMA) of randomized controlled trials (RCTs) was conducted. A search of PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) was electronically searched until the end of December 2014. Moreover, we manually checked reference lists of eligible trials and review and retrieval unpublished literature. RCTs which investigated the comparative effects of EIN versus standard enteral nutrition (EN) or different EIN regimes were included if the clinical outcomes information can be extracted from it. A total of 27 RCTs were incorporated into this study. Pair-wise meta-analyses suggested that preoperative (relative risk [RR], 0.58; 95% confidence interval [CI], 0.43–0.78), postoperative (RR, 0.63; 95% CI, 0.52–0.76), and perioperative EIN methods (RR, 0.46; 95% CI, 0.34–0.62) reduced incidence of postoperative infectious complications compared with standard EN. Moreover, perioperative EIN (RR, 0.65; 95% CI, 0.44–0.95) reduced the incidence of postoperative noninfectious complications, and the postoperative (mean difference [MD], −2.38; 95% CI, −3.4 to −1.31) and perioperative EIN (MD, −2.64; 95% CI, −3.28 to −1.99) also shortened the length of postoperative hospitalization compared with standard EN. NMA found that EIN support effectively improved the clinical outcomes of patients who underwent selective surgery for GI cancer compared with standard EN. Our results suggest EIN support is promising alternative for operation management in comparison with standard EN, and perioperative EIN regime is the optimum option for managing clinical status of patients who underwent selective surgery for GI cancer.